Study on measurement model of lignin content in pulp after alkaline extraction - Ma, Zhichao; Chen, Shaoxu; Yin, Yongjun; Zhou, Yanying; Lu, Xiaodan; Lin, Tingting (Journal of Environmental Engineering and Landscape Management, 2021)
Because kappa number cannot accurately represent the lignin content in the pulp after alkaline extraction, lead to the excessive dosage of bleaching chemicals added and the pollutant content increases. In order to accurately determine the dosage of bleaching agent, reduce pollutant emissions, a prediction model of lignin content of pulp was established by analyzing the correlation between lignin content and alkaline extraction conditions in this paper. The results show that the established soft sensor model can accurately measure lignin content, it is helpful to determine the amount of bleaching agent more accurately, reduce pollutant generation after pulp bleaching.